2016
DOI: 10.1038/srep26616
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive influence of SAMHD1 on Hepatitis B Virus life cycle

Abstract: Deoxynucleotide triphosphates (dNTPs) are essential for efficient hepatitis B virus (HBV) replication. Here, we investigated the influence of the restriction factor SAMHD1, a dNTP hydrolase (dNTPase) and RNase, on HBV replication. We demonstrated that silencing of SAMHD1 in hepatic cells increased HBV replication, while overexpression had the opposite effect. SAMHD1 significantly affected the levels of extracellular viral DNA as well as intracellular reverse transcription products, without affecting HBV RNAs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 72 publications
(135 reference statements)
4
63
2
Order By: Relevance
“…Wild-type SAMDH1 and its T592V mutant that cannot be phosphorylated both still inhibited HBV replication, while this antiviral function was lost for the dNTPase-deficient D207N and D137N mutants and the phosphomimetic mutant T592E in Huh7 cells ( Fig. 1A), which was in accordance with previous reports [19]. These results suggested that the dNTPase activity and an unphosphorylated state of SAMHD1 are both essential for restricting HBV replication.…”
Section: Resultssupporting
confidence: 91%
“…Wild-type SAMDH1 and its T592V mutant that cannot be phosphorylated both still inhibited HBV replication, while this antiviral function was lost for the dNTPase-deficient D207N and D137N mutants and the phosphomimetic mutant T592E in Huh7 cells ( Fig. 1A), which was in accordance with previous reports [19]. These results suggested that the dNTPase activity and an unphosphorylated state of SAMHD1 are both essential for restricting HBV replication.…”
Section: Resultssupporting
confidence: 91%
“…6), raising the question for its mode of action. Our data support a model in which the positive effects of VprBP for cellular and viral gene expression in infected cells are at least partially exerted via degradation of its binding partner SAMHD1, which is known to deplete cellular dNTP levels and to degrade viral RNA (56,58,77). Indeed, we detected decreased SAMHD1 expression levels during permissive Pan infection (Fig.…”
Section: Functional Validation Of Significant Protein Signatures Bysupporting
confidence: 70%
“…VprBP has been described to facilitate proteasomal degradation of SAMHD1, a known restriction factor for several human pathogens including hepatitis B virus, herpes simplex virus, vaccinia virus and retroviruses (52)(53)(54)(55)(56)(57)(58). To investigate the hypothesis that SAMHD1 is regulated in influenza virus infection we compared its expression in human cells infected with the Pan or Mal viruses, respectively, at 4 h and 16 h p.i.…”
Section: Functional Validation Of Significant Protein Signatures Bymentioning
confidence: 99%
“…Additionally, SAMHD1 has been reported to restrict the double‐stranded DNA viruses, vaccinia, and Herpes simplex virus type 1, in nondividing target cells through its dNTP triphosphohydrolase activity . The SAMHD1 inhibited replication of a third DNA virus, hepatitis B virus , in liver cells, which has been further confirmed by 2 recent studies . Moreover, it was reported that porcine SAMHD1 restricts replication of the highly pathogenic porcine reproductive and respiratory syndrome virus, which is a positive‐stranded RNA virus .…”
Section: Structure Of Samhd1 and Its Antiviral Activitymentioning
confidence: 66%
“…16,17 The SAMHD1 inhibited replication of a third DNA virus, hepatitis B virus , in liver cells, 18 which has been further confirmed by 2 recent studies. 19,20 Moreover, it was reported that porcine SAMHD1 restricts replication of the highly pathogenic porcine reproductive and respiratory syndrome virus, which is a positive-stranded RNA virus. 21 Taken together, these studies indicate that SAMHD1 broadly inhibits replication of retroviruses, DNA viruses or RNA viruses and thus, has broad antiviral activity ( Table 1).…”
Section: Structure Of Samhd1 and Its Antiviral Activitymentioning
confidence: 99%